The serotonin transporter gene (SLC6A4) shows differential regulation between children with ASD and typically developing children in a South African population - Hulley, Michaella (Department of Molecular and Cell Biology, 2017)
Autism spectrum disorders (ASD) are characterised by impairments in social interaction and communication, and repetitive and compulsive behaviours. The heterogeneous nature of ASD is underpinned by complex genetic networks; hence there is no known single genetic cause of ASD. It is therefore imperative to identify both genetic and epigenetic loci associated with ASD or specifically ASD endophenotypes. This may aid in earlier interventions for ASD if molecular biomarkers were identified. The serotonergic system has a longstanding association with ASD, and the differential expression of the serotonin transporter gene (SLC6A4) is linked to particular ASD traits. This study focuses on a length polymorphic repeat region (5-HTTLPR) upstream of the SLC6A4 promoter, and SLC6A4 promoter DNA methylation. The short variant of 5-HTTLPR is directly linked to lowered SLC6A4 expression and is at higher frequencies in ASD populations. DNA methylation at the promoter of SLC6A4 is also known to affect SLC6A4 expression. This study hypothesis is that there is differential regulation of SLC6A4, through changes in 5-HTTLPR and DNA methylation, between an ASD and control cohort. This differential regulation was also predicted to differ between ASD endophenotypes based on severity levels categorised by ADOS-2 (Autism Diagnostic Observation Schedule-2). ASD children (n=50) were compared to an agematched control group (n=13), all of whom were characterised phenotypically by an ADOS-2 assessment. The 5-HTTLPR and SLC6A4 promoter DNA methylation were analysed using restriction fragment length polymorphic analysis and the EpiTYPER assay, respectively. Significant differences were found in SLC6A4 regulation between the ASD and control group. A significant increase in frequency of individuals homozygous for the 5-HTTLPR long variant in the control group was observed when compared to the ASD cohort (p=0.049); with the long allele conferring reduced risk of ASD. Overall DNA methylation at the SLC6A4 promoter region was significantly decreased in the ASD cohort (p=0.011), the moderate ASD endophenotype (p=0.004), language impaired endophenotype (p=0.003), as well as the more severe socially and repetitive and restricted behaviour groups (p=0.006 and 0.045, respectively), when compared to the control cohort. Reduced levels of DNA methylation at CpG 30 in the target region were found to be significantly associated with higher levels of repetitive behaviour (p=0.001). The data from this study implicates the involvement of the serotonin transporter in overall ASD aetiology, specifically within the language impaired and repetitive and restricted behaviour endophenotypes. The data highlight the importance of maintaining appropriate methylation levels in order to modulate SLC6A4 expression. The regulatory mechanisms that control DNA methylation at the SLC6A4 promoter are unknown and need to be identified to completely understand how dysfunction of the serotonergic system is involved in ASD.